2001
DOI: 10.1165/ajrcmb.25.2.4383
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Inhibition of Fibroblast-Induced Gel Contraction Is Mediated by PGE2and NO Acting Through Separate Parallel Pathways

Abstract: Contraction of three-dimensional collagen gels is a model of the contraction that characterizes normal healing and remodeling after injury. In the current study, we evaluated the hypothesis that a number of inflammatory factors, including tumor necrosis factor (TNF)-alpha, interleukin (IL)-1 beta, and interferon (IFN)-gamma, modulate this process by induction of prostaglandin (PG) E(2) and nitric oxide (NO) production and that these secondary mediators function in an autocrine or paracrine manner to modulate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 26 publications
3
54
0
Order By: Relevance
“…Both fibroblast proliferation and protein production in the gels differ markedly from those in monolayer cultures (3). If the gels are floating in cell culture medium the fibroblasts will contract the gels, and this contraction can be modified by a variety of exogenous agents, which either simulate or inhibit the collagen gel contraction (11,48,54,57). In vivo, tissue remodeling is a complex process and can play an important role in many pathophysiological processes in which altered tissue structure leads to loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…Both fibroblast proliferation and protein production in the gels differ markedly from those in monolayer cultures (3). If the gels are floating in cell culture medium the fibroblasts will contract the gels, and this contraction can be modified by a variety of exogenous agents, which either simulate or inhibit the collagen gel contraction (11,48,54,57). In vivo, tissue remodeling is a complex process and can play an important role in many pathophysiological processes in which altered tissue structure leads to loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, in tissue containing multiple cell types, fibroblasts would precede endothelial cells into denuded areas (36) such that the release of arachidonate metabolites from fibroblasts to coordinate their own spreading, bridging, and migration would also likely influence surrounding endothelial, smooth muscle, and neural cells. Endothelial wound closure in small scrape wounds of corneal and vascular endothelium have been reported to occur primarily by enlargement and flattening, or spreading, of peripheral wound cells adjacent to the wound gap (10,30).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, higher doses of exogenous NO have been shown to affect proliferation rate (39) and collagen synthesis (40) and inhibit fibroblast-mediated gel contraction (41). However, high doses of NO may cause peroxynitrite formation, induce oxidative DNA damages and apoptosis (39) and impair collagen synthesis due to toxicity (40).…”
Section: Discussionmentioning
confidence: 98%